Assessing the potential for knowledge-based development in the transition countries of Central and Eastern Europe, the Caucasus and Central Asia - Reinhilde Veugelers (Bruegel, 2010)
Transition economies that formerly were within the Soviet Union's political and economic sphere had on the eve of the crisis much lower GDPs per capita than the EU15 or the United States, despite exhibiting higher growth. In part, increasing total-factor productivity (TFP), a `residual' growth factor commonly interpreted as reflecting technological progress, was behind higher growth rates. This paper zooms in on this TFP contribution to growth in the transition countries of central and eastern Europe, the Caucasus and Central Asia, in order to identify which countries have established a knowledge-based growth path or have the potential to develop one in the near future. We start by looking at how the transition countries covered by the working paper measure up according to traditional innovation input and output indicators. But the major part of our analysis focuses on identifying countries' potential for future knowledge-based growth. Few transition economies have highly-developed innovation profiles. Analysis of the prerequisites for knowledge-based growth indicates that transition countries are at a systemic disadvantage relative to the US, EU15 and Japan, and have limited potential for knowledge-based growth.
Keywords: 330; Produktivität; Wissensgesellschaft; Innovation; Wirtschaftswachstum; Transformationsstaaten; Kaukasus; Osteuropa; Zentralasien